Project management : practical tools for success - Haynes, Marion E. (Crisp Pub. Menlo ParkUS, 2002)
Discusses the 4 phases of a project viz. definition, planning, implementation and conclusion i.e completion and evaluation. Presents 7 action steps for defining the project, describes S-M-A-R-T objectives and advises on conducting a feasability study. Provides planning steps which include consideration of the quality, time and cost dimensions. Discusses implementation of the plan, looking at control, feedback, negotiation, and, resolution of differences. Includes project completion checklist, and project evaluation form. This 3rd edition emphasises the importance of effective communication, and particularly, the listening skills.